Stability analysis on synchronizing two parametrically excited chaotic oscillators by a single control function - Ahmad, Israr; Saaban, Azizan; Ibrahim, Adyda; Shahzad, Mohammad (Natural Sciences Publishing, 2016)
In chaos synchronization, a feedback controller is designed in a way that one of the chaotic oscillator completely traces the dynamics of another chaotic (master) oscillator.This paper aims to investigate the synchronization behavior between two identical chaotic gyros and two non-identical chaotic gyro and the Double-Hump Duffing-Van der Pol (DHDVP) oscillators.Based on the Routh- Hurwitz criterion and Lyapunov stability theory and using the active control strategy, a single input control function is designed that establishes the synchronization globally.The linear controller gain coefficients are determined by our own choice that ensures the globally exponential stability of the closed-loop. Effect of the unknown time varying external disturbances is under our discussions.The simulation results are carried out to verify the effectiveness of the proposed active control strategy and possible feasibility in synchronizing two identical and two non-identical chaotic oscillators.